About the Status and Prospects of Gerontology and Geriatrics in the Kyrgyz Republic - Mamatov Sagynali Murzaevich1 , Arstanbekova Mira Arstanbekovna1 , Imanalieva Farida Eldiyarovna1 , N (Institute of Medico-legal Publications Pvt Ltd, 2020)
The objective is to assess the state and prospects of development of the gerontological service and to study the level of the demographic situation in the Kyrgyz Republic. We studied Legislative, regulatory and legal documents and materials from open sources have studied since Using the example of Bishkek and Nizhne-Serafimovsk social stationary facilities, the state of health was analyzed, and 442 patients examined. Successes in the development of the gerontology: the Kyrgyz Republic became a member of the AgeNet International gerontological network (2005), the law “On Senior Citizens in the Kyrgyz Republic” (2011) was adopted, and an Action Plan to improve the quality of life of older citizens at 2019-2025. A high frequency of comorbidity revealed: 241 (56.4%) of the wards had from 1 to 3 diseases, 185 (43.3%) from 4 to 6 diseases and in 128 (29.9%) of the departments, seven or more diseases registered. The country needs to create a single coordinating body for gerontological and geriatric services, which will be responsible for its work and development.